Miocene to Holocene Marine Tephrostratigraphy Offshore Northern Central America and Southern Mexico: Pulsed Activity of Known Volcanic Complexes. (5th November 2018) - Schindlbeck, J. C.; Kutterolf, S.; Freundt, A.; Eisele, S.; Wang, K.‐L.; Frische, M.
Abstract: We studied the tephra inventory of 14 deep sea drill sites of three Deep Sea Drilling Project and Ocean Drilling Program legs drilled offshore Guatemala and El Salvador (Legs 67, 84, and 138) and one leg offshore Mexico (Leg 66). Marine tephra layers reach back from the Miocene to the Holocene. We identified 223 primary ash beds and correlated these between the drill sites, with regions along the volcanic arcs, and to specific eruptions known from land. In total, 24 correlations were established between marine tephra layers and to well‐known Quaternary eruptions from El Salvador and Guatemala. Additional 25 tephra layers were correlated between marine sites. Another 108 single ash layers have been assigned to source areas on land resulting in a total of 157 single eruptive events. Tephra layer correlations to independently dated terrestrial deposits provide new time markers and help to improve or confirm age models of the respective drill sites. Applying the respective sedimentation rates derived from the age models, we calculated ages for all marine ash beds. Hence, we also obtained new age estimates for eight known but so far undated large terrestrial eruptions. Furthermore, this enables us to study the temporal evolution of explosive eruptions along the arc, and we discovered five pulses of increased activity: (1) a pulse during the Quaternary, (2) a Pliocene pulse between 6 and 3 Ma, (3) a Late Miocene pulse between 10 and 7 Ma, (4) a Middle Miocene pulse between 17 and 11 Ma, and (5) an Early Miocene pulse (ca. >21 Ma). Key Points: This is a stratigraphically classified tephra database of glass compositions with correlations of marine and terrestrial tephra layers We provide new insights into the lifetime of the major volcanic centers in Guatemala and El Salvador and their number of major eruptions We identify five pulses of enhanced volcanic activity during the Quaternary, the Pliocene, the Late, Middle Miocene, and Early